M6. REDUCED READINESS POTENTIAL AS A NEUROPHYSIOLOGICAL CORRELATE OF SELF-DISTURBANCES IN EARLY–COURSE PSYCHOSIS: PRELIMINARY FINDINGS FROM A HIGH–DENSITY EEG STUDY. (18th May 2020) - Donati, Francesco; Carrara, Claudia; Casetta, Cecilia; del Giudice, Renata; Zalaffi, Maristella; Cornali, Mattia; Maestri, Davide; Sarasso, Simone; D'Agostino, Armando
Abstract: Background: Self-disturbances reflect a core dimension of Schizophrenia that can be identified before disease onset and might underlie the development of typical psychotic symptoms. The Sense of Agency (SoA) can be conceptualized as the pre-reflective sensation of being the one who is causing or generating an action or thought. Passivity phenomena, such as the reported feeling and belief that one's thoughts or actions are generated and/or controlled by an external agent, are exquisite examples of SoA disturbances observed in Schizophrenia. Despite intensive research, the neurobiological pathogenetic mechanisms underlying such disturbances remain unclear. Among several putative neurophysiological brain abnormalities, a reduction of the Bereitschaftspotential, also called pre-motor or Readiness Potential (RP), was described in chronic, medicated patients with Schizophrenia. Given its anticipation of voluntary movement by 1 – 2 seconds over the motor cortex and supplementary motor area contralateral to the effector, RP has previously been proposed to be a neural signature of volition to initiate movement. Interestingly, higher RPs among healthy subjects have been recently associated with stronger intentional binding, suggesting increased SoA in subjects exhibiting stronger premovement activity. The objective of our work was to study RP abnormalities in patients with a psychotic illness of recent onset and to relate them to self disturbances, in order to clarify the relationship between known neurophysiological and psychopathological abnormalities. Methods: We employed high-density electroencephalography (64-channel BrainAmp, Brain Products GmbH, Gilching, Germany) to record scalp potentials during a self-paced movement task in a group of seven early–course psychosis patients (mean age = 24, 5, range 20–33) and an equal group of age– and gender– matched (mean age =25, 3, range 19 – 36) healthy control subjects. Patients were recruited during an acute stage of their disorder requiring hospitalization and were treated with low–dose atypical antipsychotics. Exclusion criteria included major medical or neurological illness affecting the CNS and any intellectual developmental disorder. Several parameters related to the elicited RP were recorded, including maximum amplitude and slope. The Examination of Anomalous Self Experience (EASE) scale was chosen to assess Self disturbances in the patient group by an experienced clinician who was blind to the neurophysiological outcome. Results: RP was found to be reduced in patients, compared to healthy control subjects, in both its amplitude and slope (p < 0, 005) despite comparable EMG activity. EASE scores of items 'EASE-10' (a comprehensive item that reflect most prototypically the disorders of self-experience) and 'EASE-2' ("Self-Awareness") appeared to increase monotonically with the decrease of RP slope (p < 0, 05). Discussion: Our preliminary data show that disturbances of RP are present since the early course of psychotic disorders. They also suggest that such abnormalities may reflect the severity of self-disturbances in these patients. If confirmed in a larger, medication-naïve samples, our findings might clarify the underlying neural mechanisms of such abnormalities and provide a solid basis for further investigation of RP disturbances as an early biological marker for Schizophrenia spectrum disorders.